Hiding Conflict over Industry Returns : A Stakeholder Analysis of the Extractive Industries Transparency Initiative /: A Stakeholder Analysis of the Extractive Industries Transparency Initiative. (May 2009) - Bracking, Sarah, 1968-
No abstract available